Transference-focused psychotherapy in an inpatient setting for borderline personality disorders: changes in symptomatology - Torvi Abel; Moritz Happel; Franca Daerr; Carsten Spitzer; Cord Benecke; Birger Dulz (Research in Psychotherapy)
This prospective, naturalistic, longitudinal study examined changes in borderline-specific symptoms in a six-month, manualbased transference-focused psychotherapy (TFP) inpatient treatment for patients with borderline personality disorder (BPD) in comparison to a waitlist control group. 74 patients with BPD received TFP in a multi-professional inpatient setting, of whom 27 patients represented the waitlist control group. 31 patients completed six months of treatment. Borderline-specific symptoms were measured by means of the Borderline Symptom List (BSL- 23) prior to treatment (waitlist control group), at the beginning, after 3 months, and at the end of it. BSL-23 scores decreased significantly from the beginning to the end of the six-month inpatient therapy program with a medium effect size of d=0.54. There was no change in symptoms for the waitlist control group. Our findings suggest that inpatient TFP is effective in terms of the reduction of borderline-specific symptoms. In terms of this, the duration of the treatment seems to be a meaningful factor. Further research will investigate changes in specific psychodynamic aspects as well as in the follow-up measurement.